PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, KEPEMILIKAN PUBLIK, PERUBAHAN HARGA SAHAM DAN RISIKO BISNIS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PUBLIK SEKTOR KEUANGAN - Dwi Suhartanto (Jurnal Ilmiah Ekonomi Bisnis, 2015)
This study was conducted to examine the factors that affect earnings management practices are firm size, profitability, leverage, public ownership, changes in stock prices and business risks. Grouping between grading company and not grading using Index to Financial Sector Public Company by the number of samples are 38 companies. Statistical analysis used is multivariate testing, using logistic regression analysis using backward stepwise method enter and to determine the factors that significantly affect the practice of income smoothing. The results of logistic regression analysis using both methods to five independent variables are supposed to influence the practice of income smoothing, there are three variables that significantly affect income smoothing practices are firm size, NPM and business risks.Conclusion that in this study ROA, leverage, public ownership and changes in the stock price does not significantly affect the income smoothing practices. As for the variable size of the company, NPM and business risk significantly affect the income smoothing practices. Keywords: firm size, profitability, leverage, public ownership, changes                      stock price, earnings management